An Approach to Automating User Story Management for Testing Process Optimization in Large Distributed Teams - Trindade, Vitor Augusto Aguiar; Souza, Mateus Luiz de Oliveira; Oliveira, Hermann Jacques Hernani de; Souza, Luiz Henrique Aquino de; Pereira, Bruno Cerdeira; Nascimento, José Carlos Rangel do; Collins, Eliane (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15053, 2025)
Efficiently managing user stories during the testing process is crucial in large, distributed test teams to ensure timely and high-quality project completion. Manual control of tasks, from various software testing activities to extracting specific quality metrics and maintaining test processes, is time-consuming and error-prone. This paper proposes an approach to automate story creation for the Jira tool to address these challenges. The proposal approach aims to optimize the time spent on story creation, promote efficiency, and increase the success rate of story creation from 73.43% to 99.66% in the story management process. The script developed establishes a secure connection with Jira, imports data from spreadsheets, populates these into Jira, and creates or updates test tasks. Additionally, JavaScript (JS) code automates data transfer from task creation to planning. This automation significantly reduces manual effort and minimizes human errors, due to the improvement in the success rate to 98.14%, and increases the productivity of the software testing team by 15.19%.